151 Sex Differences in the Maturational Trajectories of Sleep Spindles in the Transition from Childhood to Adolescence. (3rd May 2021) - Ricci, Anna; He, Fan; Younes, Magdy; Calhoun, Susan; Fang, Jidong; Houser, Lyndsey; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward; Fernandez-Mendoza, Julio
Abstract: Introduction: Sleep spindles occur as bursts of EEG activity in the sigma (11-16 Hz) frequency range and are purported biomarkers of cortical development. However, the few studies examining maturational changes in sleep spindles are limited by small samples and/or short follow-up periods. Thus, large longitudinal population-based studies are needed to determine their developmental trajectories as the child transitions to adolescence. Methods: We analyzed the sleep EEG of 572 un-medicated subjects aged 6-21 (47.6% female, 25.9% racial/ethnic minority), of whom 332 were 5-12 years at baseline and followed-up at ages 12-22. Multivariable-adjusted models tested the cross-sectional and longitudinal trajectories of sleep spindle density, frequency, and power. Results: From age 6 to 21, the trajectory of sleep spindle density was best fit by a quadratic model (p=0.02), particularly in males (p-quadratic=0.05). Females maintained more stable levels of sleep spindle density (p-linear=0.26), as shown by a longitudinal increase 37.6% lower than males by age 14 (p=0.01). Sleep spindle frequency increased (p-linear<0.01), while sleep spindle power decreased (p-linear<0.01), from age 6 to 21. The trajectory of sleep spindle frequency diverged between females (p-linear<0.01) and males (p-quadratic=0.02), in whom it plateaued by age 15 onwards. Females had experienced a longitudinal increase in sleep spindle frequency 2.4% higher than males by age 20-22 (p=0.05). Males had experienced a steeper decreasing slope in sleep spindle power (p-linear<0.01) than females (p-linear=0.12), as confirmed by a longitudinal decline 25.4% greater than females by age 19 (p=0.02). Conclusion: Sleep spindle metrics follow distinct maturational trajectories from each other and from other EEG oscillations (e.g., slow wave activity). The increase in sleep spindle density from childhood to early adolescence coupled with the linear increase in sleep spindle frequency from childhood to young adulthood may represent the emergence of fast sleep spindles, which appears to occur earlier in females. Overall, males experience greater maturational changes in all sleep spindle metrics and sex differences become prominent in young adulthood, when males show lower sleep spindle density and sleep spindle frequency, indicative of less fast sleep spindles. Support (if any): NIH Awards Number R01MH118308, R01HL136587, R01HL97165, R01HL63772, UL1TR000127